Synthesis, magnetic and ethanol gas sensing properties of semiconducting magnetite nanoparticles - Al-Ghamdi, Ahmed A.; Al-Hazmi, Faten; Al-Tuwirqi, R. M.; Alnowaiser, F.; Al-Hartomy, Omar A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Elsevier, 2013)
The superparamagnetic magnetite (Fe3O4) nanoparticles with an average size of 7 nm were synthesized using a rapid and facile microwave hydrothermal technique. The structure of the magnetite nanoparticles was characterized by X-ray diffraction (X-ray), field effect scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDS), and transmission electron microscopy (TEM). The prepared Fe3O4 was shown to have a cubic phase of pure magnetite. Magnetization hysteresis loop shows that the synthesized magnetite exhibits no hysteretic features with a superparamagnetic behavior. The ethanol gas sensing properties of the synthesized magnetite were investigated, and it was found that the responsibility time is less than 10 s with good reproducibility for ethanol sensor. Accordingly, it is evaluated that the magnetite nanoparticles can be effectively used as a solid state ethanol sensor in industrial commercial product applications. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Semiconducting magnetite nanoparticles; Magnetic properties; Ethanol gas sensor